A phase 1b study of placenta‐derived mesenchymal stromal cells in patients with idiopathic pulmonary fibrosis. Issue 7 (9th July 2014) - Chambers, Daniel C.; Enever, Debra; Ilic, Nina; Sparks, Lisa; Whitelaw, Kylie; Ayres, John; Yerkovich, Stephanie T.; Khalil, Dalia; Atkinson, Kerry M.; Hopkins, Peter M.A.
Abstract Background and objective Idiopathic pulmonary fibrosis (IPF) is a degenerative disease characterized by fibrosis following failed epithelial repair. Mesenchymal stromal cells (MSC), a key component of the stem cell niche in bone marrow and possibly other organs including lung, have been shown to enhance epithelial repair and are effective in preclinical models of inflammation‐induced pulmonary fibrosis, but may be profibrotic in some circumstances. Methods In this single centre, non‐randomized, dose escalation phase 1b trial, patients with moderately severe IPF (diffusing capacity for carbon monoxide (DLCO) ≥ 25% and forced vital capacity (FVC) ≥ 50%) received either 1 × 106 (n = 4) or 2 × 106 (n = 4) unrelated‐donor, placenta‐derived MSC/kg via a peripheral vein and were followed for 6 months with lung function (FVC and DLCO), 6‐min walk distance (6MWD) and computed tomography (CT) chest. Results Eight patients (4 female, aged 63.5 (57–75) years) with median (interquartile range) FVC 60 (52.5–74.5)% and DLCO 34.5 (29.5–40)% predicted were treated. Both dose schedules were well tolerated with only minor and transient acute adverse effects. MSC infusion was associated with a transient (1% (0–2%)) fall in SaO2 after 15 min, but no changes in haemodynamics. At 6 months FVC, DLCO, 6MWD and CT fibrosis score were unchanged compared with baseline. There was no evidence of worsening fibrosis. Conclusions Intravenous MSC administration is feasible and has a good short‐term safety profile in patients with moderately severe IPF.